Analysis of deactivation models based on Time-on-Stream (TOS) Theory for fluid catalytic cracking process - Felipe López Isunza (Journal of the Mexican Chemical Society, 2000)
The deactivation of equilibrium catalyst for catalytic cracking of vacuum gas oil was studied via MAT experiments with industrial catalyst and feedstock using the 3-lump kinetic scheme proposed by Weekman [1] and five deactivation models reported inliterature based on Time-on-Stream (TOS) Theory (Model 1, exponentiallaw; Model 2, a second-order model; Model 3, power law; Model 4, hyperbolic function; Model 5, an empirical model). The five deactivation models can be derived from a general m-order expression. All the models can represent the experimental data except the second-order model.